ANALISIS KESIAPAN MADRASAH DALAM MENGHADAPI PELAKSANAAN ASESMEN KOMPETENSI MADRASAH INDONESIA (AKMI) - Mega Dwi Susanti; Aida Rohmatin (Salimiya: Jurnal Studi Ilmu Keagamaan Islam, 2024)
This research is motivated by government policy in changing National Examination activities to AKM. In this policy, the Ministry of Religion, as the institution that oversees religious education, added a program in the form of the Indonesian Madrasah Competency Assessment (AKMI). This research aims to determine the readiness of madrasas and find out the obstacles experienced by madrasas in facing the Indonesian Madrasah Competency Assessment (AKMI) at MI Al-Islahiyah Bobosan. This type of research is field research with a descriptive design with a qualitative approach. Data collection techniques were carried out using observation, interviews and documentation. The informants who have been determined are the Madrasah Principal, Class V Teacher and Class V Students. The data that has been obtained is analyzed descriptively by means of data reduction, data presentation and drawing conclusions. The results of this research found that teacher readiness in facing the Indonesian Madrasah Competency Assessment (AKMI), namely 1) Availability of supporting books in preparation for implementing AKMI, 2) Having a reading corner, 3) Providing additional study hours, 4) Implementing learning strategies and methods 5 ) Providing motivation and appreciation for students' abilities 6) Availability of Lab facilities. Computer. Students' readiness to face the Indonesian Madrasah Competency Assessment (AKMI), namely 1) Able to manage time, 2) Learn to be able to master the material well, feel capable, confident and ready, 3) Always remember Allah, by always praying before doing questions -about AKMI. The obstacles that madrasas experience are a) Damage to the computers that will be used in AKMI activities b) Preparation of teachers and students for learning c) Unstable internet network. d) Arouse students' enthusiasm for literacy.